Economic Importance and Production Problems of White Lupin - Halász, András (Acta Agraria Debreceniensis, 2003)
This paper presents economical importance of white lupin /Lupinus albus/. It is an important task as exceptional effectual green manure, that shows VIII treatment’s results of Westsik long-term field experiment. Content of white lupin seed is similar than content of soybean. By the forrage examination the soybean can substitute whit white lupin seed in 40%. The main problem of the production of lupin seed is the want of long term herbicides. For the solve of this problem to find herbicides which are efficiant for 80-100 days. First we have try 26 different herbicides.